2023
DOI: 10.1097/ju.0000000000002942
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Supplementation on Overactive Bladder and Urinary Incontinence Symptoms in Older Men: Ancillary Findings From a Randomized Trial

Abstract: Purpose:Our goal was to evaluate vitamin D supplementation for preventing or treating overactive bladder and urinary incontinence in men.Materials and Methods:Ancillary study of men aged ≥55 years in VITAL (VITamin D and OmegA-3 TriaL). Randomized treatments included: vitamin D3 (cholecalciferol), marine omega-3 fatty acids, or matching placebo. Structured urinary incontinence questions measured the prevalence of overactive bladder at year 5 and urinary incontinence at years 2 and 5, along with incidence and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(45 reference statements)
1
4
0
Order By: Relevance
“…Despite VDS not demonstrating improvements in preventing or treating OAB compared to placebo among men, the targeted utilization of VDS in men with lower 25(OH)D levels yielded indeterminate results. 12 Similar to previous findings in children, our results also suggested that the subset with lower vitamin D levels (below 20 ng/mL) demonstrated an augmented voiding frequency at the initial visit and a heightened effectiveness compared to the cohort possessing higher vitamin D levels (20-35 ng/mL) after VDS intervention. 14 No discernible difference emerged in the primary outcomes between the “never group” and the “ever group,” stratified by their VDS history, nor between the “worse response group” and the “better response group,” categorized by whether vitamin D levels surpassed 10 ng/mL following supplementation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite VDS not demonstrating improvements in preventing or treating OAB compared to placebo among men, the targeted utilization of VDS in men with lower 25(OH)D levels yielded indeterminate results. 12 Similar to previous findings in children, our results also suggested that the subset with lower vitamin D levels (below 20 ng/mL) demonstrated an augmented voiding frequency at the initial visit and a heightened effectiveness compared to the cohort possessing higher vitamin D levels (20-35 ng/mL) after VDS intervention. 14 No discernible difference emerged in the primary outcomes between the “never group” and the “ever group,” stratified by their VDS history, nor between the “worse response group” and the “better response group,” categorized by whether vitamin D levels surpassed 10 ng/mL following supplementation.…”
Section: Discussionsupporting
confidence: 90%
“…10,11 Further, recent studies have demonstrated that vitamin D supplementation (VDS) could ameliorate urinary tract symptoms in specific adult populations. 12 A systematic review and meta-analysis confirmed the safety of high-dose VDS among children aged 0 to 6 years. 13 Moreover, a recent trial showed a treatment benefit of high-dose VDS in reducing OAB-related incontinence in children with vitamin D deficiency.…”
mentioning
confidence: 87%
“…Increasing evidence has demonstrated that diet plays a critical role in OAB management. Some research suggested that people with low vitamin D intake had a high risk of OAB via muscle atrophy (17). A clinical study revealed that low vitamin B6 and B12 often coupled with elevated plasma homocysteine concentrations resulting from impaired homocysteine metabolism, may contribute to the development of CVD and neurodegenerative disorders (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, an association with vitamin D deficiency and urinary symptoms has been reported mostly in adults with mixed results on whether treatment with vitamin D is effective. 2 There is also literature regarding vitamin D deficiency as a cause of constipation and other bowel symptoms. 3…”
mentioning
confidence: 99%